The dynamics of women’s representation in legislative body of Tasikmalaya City, West Java Indonesia - Widyawati Widyawati (Masyarakat, Kebudayaan dan Politik, 2022)
Women’s representation in the legislative body has a significant role in increasing democratic quality. This is because democracy necessitates the equality between men and women in political spheres, including in the legislative body. This article aims to critically analyze women’s representation in the legislative body in Tasikmalaya City and examine the implementation of affirmative action through 30% quota for women. The method used in this research is content analysis companied with political approach. As for the data, this article utilizes primary and secondary data collected through in-depth interview and library research, respectively. In addition, the data were analyzed through the concept of representation proposed by Pitkin as well as an integrated model of women’s representation used by Schwindt-Bayer and Mishler. This study reveals that women’s representation in a political position, such as parliament, does not merely depend on affirmative action through legal rules, it is also influenced by political, socioeconomic and ideological-psychological factors. This study concludes that women’s underrepresentation in parliament of Tasikmalaya City is caused not by a single factor, but by various factors such as education, religious and patriarchal beliefs as well as competencies of women candidates.